Pemanfaatan Aplikasi dan Software Digital terhadap Kebutuhan Evaluasi Pembelajaran Pendidikan Agama Islam - Sahrul Sobirin; Mohammad Ihsan; Wahab Wahab (LP. Ma'arif Janggan Magetan, 2023)
As a society that lives in the era of technology, of course, we must be able to make good use of the presence of these technological advances, especially in educational institutions. This is also inseparable from the role of a teacher who is also required to be able to utilize all the presence of technology well. Starting from the learning process to the evaluation of learning. Seeing from the number of software that can be used for the learning process and evaluation materials, the author considers it necessary to describe what software can be used for learning evaluation in the current era. The method in this study uses a qualitative approach with library research methods. The purpose of making this article is to find out how to use applications or software in learning evaluations consisting of Quiziiz, Google forms and Kahoot. The result of this research is how we utilize applications and software in educational institutions starting from learning, administration, and evaluation of learning which is actually a must for all of us because at this time we are already in an era where everything has used technology. Not only that, for students in today's era, it can be said that he has known the name of technology from an early age. For example, in kindergarten educational institutions that currently have a lot of use of technological advances.